2011
DOI: 10.1093/cercor/bhr035
|View full text |Cite
|
Sign up to set email alerts
|

A Pure Salience Response in Posterior Parietal Cortex

Abstract: When exploring a visual scene, some objects perceptually popout because of a difference of color, shape, or size. This bottom-up information is an important part of many models describing the allocation of visual attention. It has been hypothesized that the lateral intraparietal area (LIP) acts as a "priority map," integrating bottom-up and top-down information to guide the allocation of attention. Despite a large literature describing top-down influences in LIP, the presence of a pure salience response to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 56 publications
1
63
0
Order By: Relevance
“…For example, V4 neurons signal the presence of an oddball too late (∼85-100 ms poststimulus) to be the source of the saliency representation observed in SCs (∼65 ms poststimulus) (10). Similarly, estimates of a pure saliency response in LIP emerge too late (∼70-75 ms poststimulus onset) (13) to be the source of the saliency representation in SCs, other than the fact that LIP does not project to SCs (24,25). It is also worth mentioning that the timing of the V1 saliency representation in our study is very similar to the timing of V1 figure-ground modulation (40,41), both of which indicate a modulation that only occurs well after the initial transient visual response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, V4 neurons signal the presence of an oddball too late (∼85-100 ms poststimulus) to be the source of the saliency representation observed in SCs (∼65 ms poststimulus) (10). Similarly, estimates of a pure saliency response in LIP emerge too late (∼70-75 ms poststimulus onset) (13) to be the source of the saliency representation in SCs, other than the fact that LIP does not project to SCs (24,25). It is also worth mentioning that the timing of the V1 saliency representation in our study is very similar to the timing of V1 figure-ground modulation (40,41), both of which indicate a modulation that only occurs well after the initial transient visual response.…”
Section: Discussionmentioning
confidence: 99%
“…1A, yellow), which is thought to be the core determinant of attention and gaze (4,5). To date, most studies have reported evidence of saliency and/or priority maps in a distributed network of cortical brain areas [e.g., primary visual cortex (V1) (6)(7)(8)(9), visual area 4 (V4) (10), lateral intraparietal area (LIP) (11)(12)(13), and frontal eye fields (14,15)]. However, there is mounting evidence for a subcortical saliency mechanism in the premammalian optic tectum (16)(17)(18) or superior colliculus (SC) in primates (Fig.…”
mentioning
confidence: 99%
“…The findings in this study show correlation of responding speed in both frontal and parietal regions, i.e., intensive modulation is associated with faster behavior. Recent evidences show earlier and more dominant neural association in parietal in such exogenous processing comparing with frontal area [19], [20]. Future studies will explore the causal influence between different frontal and parietal regions to find the information flows that are correlated with the reaction time, given the advantage of high temporal resolution of EEG data.…”
Section: Discussionmentioning
confidence: 98%
“…after 400 ms). A decrease in the beta power (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) is also clear in these two electrodes, appearing at about 300 ms, continuing during lane change behavior. In addition, a late increase at about 500 ms can be observed in the low frequency (1-4 Hz) activity in FCz.…”
Section: Power Spectral Densitymentioning
confidence: 98%
“…Previous single cell studies in non-human primates have suggested that single neurons in area LIP of the parietal lobe are modulated by bottom-up as well as top-down attention (Buschman and Miller, 2007;Arcizet et al, 2011), and that they are sensitive to signals such as probability of reward (Sugrue et al, 2004). It has been proposed that the parietal cortex possesses a saliency map of visual space for target selection (Koch and Ullman, 1985;Gottlieb et al, 1998;Itti and Koch, 2000;Treue, 2003).…”
Section: Scaling Of Erfs Following Stimulus Rankmentioning
confidence: 99%